Зеркало смерти: роман / Анна Малышева ; худ. И. А. Озеров - Малышева Анна Витальевна (Криминальный талант, 2003)
Экземпляры: ФО-5 (20110413) / Инвентарный номер: 46872 / Цена: 63.00 / Сис.шифр: 84(2Рос=Рус)6 46872 / Авт.знак: М 20 / ББК: 84(2Рос=Рус)6